A Novel Proliposomal Ropivacaine Oil: Pharmacokinetic–Pharmacodynamic Studies After Subcutaneous Administration in Pigs. (May 2016) - Davidson, Elyad M.; Haroutounian, Simon; Kagan, Leonid; Naveh, Michael; Aharon, Arnon; Ginosar, Yehuda
Abstract : BACKGROUND: Liposomal local anesthetics are limited by a short liposomal shelf-life, even when under refrigeration. We describe a novel proliposomal ropivacaine that produces liposomes in situ, only after exposure to aqueous media. METHODS: In vitro: Nanoparticles were assessed (particle size distribution analyzer, cryo-transmission electron microscopy) at baseline and after exposure to saline/plasma. Toxicity: In porcine wound healing study ( n = 12), healing was assessed by photography, clinical assessment, and histology. Pharmacodynamics: Seventeen young piglets were randomly assigned to plain 0.5% ropivacaine ( n = 5), proliposomal 4% ropivacaine ( n = 6), or sham ( n = 6). Tactile threshold was assessed using von Frey filaments applied to the surgical wound; the nonoperated skin was used as a control. Tactile threshold over time was determined using area under the curve (AUC) and assessed by 1-way analysis of variance. Pharmacokinetics: 8 young piglets were randomly assigned to plain 0.5% (25 mg, n = 4) or proliposomal 4% (200 mg, n = 4) ropivacaine. Plasma ropivacaine was assessed by high-performance liquid chromatography at baseline and at intervals over 36 hours. Paired ropivacaine concentration (from wound exudate and plasma) was obtained at 96 hours. Data were analyzed using noncompartmental and compartmental models. RESULTS: In vitro: On exposure to saline and plasma, the study drug was transformed from a homogenous oil to an emulsion containing liposomes of approximately 1.4-μm diameter; this effect was dilution dependent and stable over time. Toxicity: All wounds healed well; no effect of drug group was observed. Pharmacodynamics: Plain and proliposomal ropivacaine provided sensory anesthesia for approximately 6 and 30 hours, respectively. There was an approximately 7-fold increase in the AUC of anesthesia for proliposomal ropivacaine compared with plain ropivacaine (mean difference, 1010; 95% confidence interval [CI], 625–1396 g·h/mm 2 ; P < 0.0001). Pharmacokinetics: There was no difference in C max (2.31 ± 0.74 vs 2.32 ± 0.46 mg/L), despite an approximately 8-fold difference in dose. However, proliposomal ropivacaine was associated with a marked prolongation of T max (6.50 ± 6.35 vs 0.5 ± 0.0 hours), terminal half-life (16.07 ± 5.38 vs 3.46 ± 0.88 hours; P = 0.0036), and ropivacaine-time AUC (47.72 ± 7.16 vs 6.36 ± 2.07 h·mg/L; P < 0.0001), when compared with plain ropivacaine. The proliposomal formulation provided an approximately 250-fold higher ropivacaine concentration in the surgical wound (mean difference, 3783 ng/mL; 95% CI, 1708–5858; P = 0.001) and an approximately 25-fold higher wound:plasma ropivacaine concentration ratio (mean difference, 126; 95% CI 38–213; P = 0.011). CONCLUSIONS: Proliposomal ropivacaine exerted prolonged anesthesia with delayed elimination, typical for liposomal drugs. The advantage of this novel proliposomal ropivacaine is its ease of preparation and its extended shelf-stability (>2 years) at room temperature. Abstract : Supplemental Digital Content is available in the text.